Integration of analytic network process with service measurement index framework for cloud service provider selection. (23rd April 2017) - Tripathi, Atul; Pathak, Isha; Vidyarthi, Deo Prakash
Summary: The growing popularity of cloud services has attracted large number of business organizations to enter into the cloud market. The varied availability of cloud service providers, for various services, leaves the cloud customers into skepticism. Service measurement index (SMI) framework, which is based on the analytic hierarchical process, is developed for the ranking of cloud services. As there are multiple dependencies among the criteria for the selection of cloud service provider, analytic hierarchical process formulation is not efficient. In the proposed work, analytic network process that captures the cloud service‐provider selection problem in a more realistic way is integrated in the ranking component of SMI framework. In this method, interactions among the criteria are used for the ranking of the cloud services. Few new criterions are also added into the existing SMI framework to make the framework more effective. A case study is conducted to analyze the proposed technique for the cloud provider selection.